Μικρού Μήκους Ντοκιμαντέρ: No clue about the future - (:unkn) unknown (My University, 2021)
Η παρούσα εργασία αφορά τo ντοκιμαντέρ μικρού μήκους ”no clue about the future”, που γυρίστηκε τη χρονία 2020/2021. Επιχειρεί να αναδείξει όψεις της καθημερινής ζωής στον προσφυγικό καταυλισμό της Σάμου, εστιάζοντας στο πορτρέτο ενός ανθρώπου που ζεί εκεί και αναλαμβάνει το ρόλο του δασκάλου. Η υλοποίηση του ντοκιμαντέρ έγινε με βάση τη μέθοδο του Κινηματογράφου της Παρατήρησης.

The present thesis is based on short film documentary "No clue about the future", which was filmed in 2020/2021. The goal of this film is to bring to light aspects of the everyday life in the refugee camp of Samos, focusing on the portrait of an asylum seeker who lives in the camp and takes on the role of a teacher. The documentary ’s filming style is inspired by the Cinema of Observation.
Short Film Documentary: No clue about the future
Keywords: ντοκιμαντέρ, Κινηματογράφος της Παρατήρησης, Σάμος, πρόσφυγες, προσφυγικός καταυλισμός, σχολείο, αυτοοργανωμένο σχολείο, δάσκαλος; documentary, Cinema of Observation, Samos, refugees, refugee camp, school, self-organised school, teacher